(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Underground mining operations in geologically complex deposits require innovative and efficient extraction methods. This study evaluates the effectiveness of combined mining systems in such environments, focusing on productivity, cost, safety, and environmental impact. A comparative analysis is conducted using data from selected caase studies and simulation models.